A rare presentation of prostate adenocarcinoma metastatic to the maxilla - Venkata S Prathi; Rakesh K Manne; Kannan Natarajan; Beeraka Swapna (Wolters Kluwer Medknow Publications, 2017)
Metastatic tumors of the orofacial region are uncommon and may occur in the oral soft tissues and jaw bones. The occurrence of prostate as the primary site for jaw metastasis is extremely rare. Mandible and palate are the common prostate metastatic sites. Here, we present a rare case of prostate adenocarcinoma metastatic to maxilla.